TO THE QUESTION OF OPTIMISING THE DYNAMIC CHARACTERISTICS OF A VIBRATIONAL TREE UPROOTING MACHINE - A. R. Mikhitarov; V. L. Savich; V. K. Khegai (Вестник Дагестанского государственного технического университета: Технические науки, 2018)
Objectives Following logging operations, tree stumps remain in the site of the former forest.While these may be uprooted by special machines in the course of forestry operations, the use of heavy forestry machines operated repeatedly on the forest sites not only lead to soil erosion, but also to considerable financial expense. Consequently, the development of machines combining cutting (logging) and uprooting operations – that is, uprooting the trees along with their roots – are of a great interest. As research has shown, the main disadvantages of the use of such technology by “conventional” logging or forestry machines are their excessive loading and energy intensity. The aim of the research is to investigate means of eliminating these drawbacks by using vibration.Methods The article deals with theproblem of ensuring the effectiveness of the vibration application – in particular, torsional vibrations, used to stub trees together with their roots. To solve this problem, a mathematical model of the “machine-tree-soil-root system” system was developed, which takes into account the mutual influence of the dynamic characteristics of the machine’s technological equipment and tree and soil-root system, which allows a rational (optimal) frequency range of vibration equipment to be selected by analysing the amplitude-frequency characteristics of a given system. To analyse the amplitude-frequency characteristics of a mechanical system, the Euler-Lagrange equationswere used.Results Based on the mathematical model of the “machine-tree-soil-root system (SRS)” system and an analysis of the amplitude-frequency characteristics of a given system, a rational range of vibration frequencies was determined. As shown by analysis, the work of vibrational equipment in a given frequency range can significantly reduce the dynamic loading of the machine and at the same time create appropriate conditions for the effective destruction of the soil-root system.Conclusion The proposed method allows the rational values of the frequency characteristic of vibration equipment for each calculated tree to be found depending on the soil type and the basic machine.